Development of a Molecular Platform for GMO Detection in Food and Feed on the Basis of “Combinatory qPCR” Technology - Broeders, Sylvia; Papazova, Nina; Bulcke, Marc Van den; Roosens, Nancy (IntechOpen, 2012)
None